Designing An Information System For Inventory Of Goods And Sales Of Fashion Products At Ma'arif Sukawening Vocational School Based On Mobile Web - Umamah , Ai; Rostika, Sri (RISTEC : Research in Information Systems and Technology, 2023)
An information system for inventory of goods and product sales is a must that must be owned by a private or state agency engaged in the education sector, especially in Vocational High Schools (SMK) which have products that can be sold so that transaction data related to inventory can be processed. effectively and efficiently, it is known that the implementation of the inventory system and product sales at SMK Ma'arif Sukawening still uses manual data processing systems such as the length of time to search for item data, product sales, product purchase data and search for product stock that has run out or will run out, product purchase returns are not controlled and there are also frequent errors in the process of making reports in calculations, product inventory, and eligibility of goods or products that are still ineffective. To be able to process large amounts of transaction data, special tools are needed to be able to handle it, therefore computers are the right choice from all sides. In terms of speed, accuracy and accuracy with the help of software that supports it, an inventory information system and product sales were built using the RUP (Rational Unified Process) system development method which went through several stages of the process, namely: Inception, Elaboration (expansion/design), Construction (Construction), and Transition (Transition). The result of this research is to build an application that is able to help process transactions more easily and efficiently which can help related parties in carrying out their business activities.